Benzodiazepines in sport, an underestimated problem: Recommendations for sports medicine physicians’ practice - Zandonai, Thomas; Peiró, Ana María; Fusina, Francesca; Lugoboni, Fabio; Zamboni, Lorenzo (Frontiers in Psychiatry, 2022)
In the last years, only few studies in literature have focused on the use and abuse of benzodiazepines (BZDs) in sport. Benzodiazepine-related problems include misuse, addiction, driving impairments, and morbidity and mortality related to overdose and withdrawal. Two clinical cases regarding elite endurance athletes evidenced that they had started to use BZDs to counteract insomnia, to recover faster from training sessions and to manage muscle pain. One of the important points that emerged from their stories was that their sports doctors did not recognize the drugs’ addictive properties, and did not intervene to gradually reduce the dosage. Experts have previously provided recommendations for BZD therapy management in clinical practice. In this article, we would like to address sports medicine physicians specifically and provide guidelines to help them manage situations involving BZD prescription, the recognition of addiction, and intervention strategies.